1999
DOI: 10.3168/jds.s0022-0302(99)75424-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Menaquinones by Lactic Acid Bacteria

Abstract: Lactic acid bacteria were examined for their ability to produce quinone compounds, which may include dietary sources of menaquinones. Isoprenyl quinones in bacterial cells grown in a synthetic medium were extracted and analyzed by thin layer chromatography. Lactococcus lactis ssp. cremoris (three strains), Lactococcus lactis ssp. lactis (two strains), and Leuconostoc lactis were selected as high producers of quinone that synthesized more than 230 nmol of quinones/g of dried cells. The quinones were presumed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 18 publications
5
79
0
Order By: Relevance
“…Whittenbury (1964) argued that its haem-dependent cytochrome may be a rudimentary respiratory system. In several lactic acid bacteria, enzymes involved in the TCA cycle, cytochromes, haem-dependent catalase and quinones, have been found (Whittenbury, 1964;Pritchard & Wimpenny, 1978;Morishita et al, 1999;Wang et al, 2000). The present isolates also could have evolved to lactic acid bacteria by following independent but similar evolutionary processes within the HA group, while retaining physiological characteristics consistent with the physico-chemical factors of salt concentration and pH that prevail in marine environments.…”
Section: Carbon Compoundmentioning
confidence: 99%
“…Whittenbury (1964) argued that its haem-dependent cytochrome may be a rudimentary respiratory system. In several lactic acid bacteria, enzymes involved in the TCA cycle, cytochromes, haem-dependent catalase and quinones, have been found (Whittenbury, 1964;Pritchard & Wimpenny, 1978;Morishita et al, 1999;Wang et al, 2000). The present isolates also could have evolved to lactic acid bacteria by following independent but similar evolutionary processes within the HA group, while retaining physiological characteristics consistent with the physico-chemical factors of salt concentration and pH that prevail in marine environments.…”
Section: Carbon Compoundmentioning
confidence: 99%
“…Humans obtain the daily nutritional requirement for vitamin K through the dietary phylloquinone that exists in plants, and, to some extent, through bacterially produced polyisoprenyl-containing compounds called menaquinones created in the human gut [68]. LAB were examined for their ability to produce quinone compounds, as vitamin K occurred naturally in two forms, namely, K1 (phylloquinone) in green plants, and K2 (menaquinones) in animals and some bacteria [69].…”
Section: Biosynthesis Of Vitamin Kmentioning
confidence: 99%
“…Morishita and coworkers published a study in 1999 that showed the possibility of producing MK-8 and MK-9 with Lactocouccus lactis ssp. cremoris YIT2011 and MK-9 and MK-10 with Lactococcus lactis YIT 3001 (29-123 μg of menaquinone/L of the fermented medium) [38]. Additionally, several patents for Lactococcus capable of producing a significantly increased amount of vitamin K2 have been deposed.…”
Section: Propionibacterium Freudenreichii Cheesementioning
confidence: 99%
“…lactis, and Leuconostoc lactis are used as starter cultures in semihard and soft cheeses. It was reported that these species produce menaquinone and MK-7 to MK-9 in particular for Lactococcus and MK-7 to MK-10 for Leuconostoc [2,38]. For example, the starter cultures CHN211 and CHN22 from Hansen, which contain these species, produce MK-4 to MK-10; MK-9 is the main menaquinone with 472.4 ± 22.6 μg/100 g cells and 390.3 ± 10.4 μg/100 g cells, respectively [35].…”
Section: Production Of Different Menaquinones By Microorganisms In Foodmentioning
confidence: 99%